TEORI BELAJAR MULTIPLE INTELEGENSI - Kamila, Nada; Banis, Santi; Hakki, Nurul; Amalia, Afni (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
This article reviews the learning theory of multiple intelligence or concentric intelligence. The method used is with a qualitative approach and type of research study library. As for the purpose of this article is to understand the theory of learning multiple intelligences that has its own basic concepts that encompass a variety of other complex intelligence such as mathematical logical linguistic intelligence, spatial kinesthetic, intrapersonal interpersonal, naturalistic intelligence and existential intelligence. This intelligence also has some special characteristics, this concise intelligence has to do with the application of the educator in an inclusive way, so that educators can understand the abilities of each child. Multiple intelligence has advantages and disadvantages in the field of education, as it requires new innovations to support the development of this theory